2016
DOI: 10.7860/jcdr/2016/19956.7936
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Pseudoaneurysm- A Death Defying Entity

Abstract: A pseudoaneurysm refers to a contained rupture of the myocardium with a tenuous pericardium walling off the leak. It needs to be differentiated from a true aneurysm by the fact that there is lack of myocardial tissue in the wall of a pseudoaneurysm. The differentiation between the two is pertinent as true aneurysms can be treated medically while pseudoaneurysms require urgent surgical treatment. Untreated pseudoaneurysms carry a high risk of rupture and mortality. We report a case of cardiac pseudoaneurysm dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Aside from these guidelines, studies have indicated that narrow neck LVPAs may spontaneously resolve and be treated medically with dual antiplatelet therapy, statins, β-blockers, and diuretics. 4 5 6 Therefore, medical management may be a viable option for patients with chronic small stable LVPAs or patients for which surgical intervention is too high risk. Surgical repair has a 23% mortality rate; however, the risk of rupture from untreated LVPAs is 30 to 45% and may be as high as 50% at 2 years, which often drives the decision to pursue surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from these guidelines, studies have indicated that narrow neck LVPAs may spontaneously resolve and be treated medically with dual antiplatelet therapy, statins, β-blockers, and diuretics. 4 5 6 Therefore, medical management may be a viable option for patients with chronic small stable LVPAs or patients for which surgical intervention is too high risk. Surgical repair has a 23% mortality rate; however, the risk of rupture from untreated LVPAs is 30 to 45% and may be as high as 50% at 2 years, which often drives the decision to pursue surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In left ventricular (LV) ruptures with pseudoaneurysm, surgical repair is superior to conservative management [22 , 23] . Additionally, the risk of stroke from an untreated LV pseudoaneurysm poses a significant risk from the accumulating thrombus [24] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a pseudoaneurysm is bounded only by the pericardium, and they should be managed aggressively as they have higher risks of rupture and hemodynamic compromise. [ 4 5 ]…”
Section: Discussionmentioning
confidence: 99%